2021
DOI: 10.1038/s41388-021-01679-8
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinase (DUB) USP13 promotes Mcl-1 stabilisation in cervical cancer

Abstract: Protein ubiquitination is a critical regulator of cellular homeostasis. Aberrations in the addition or removal of ubiquitin can result in the development of cancer and key components of the ubiquitination machinery serve as oncogenes or tumour suppressors. An emerging target in the development of cancer therapeutics are the deubiquitinase (DUB) enzymes that remove ubiquitin from protein substrates. Whether this class of enzyme plays a role in cervical cancer has not been fully explored. By interrogating the ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 79 publications
0
37
0
Order By: Relevance
“…MCL1, a pro-survival and pro-proliferative factor, plays a critical role in many tumor types. The deubiquitination and stabilisation of MCL1 was considered to be required for the proliferation of CC cells ( Morgan et al, 2021 ). What’s more, MCL1 siRNA-silencing demonstrated high efficacy on CC cell lines ( Lechanteur et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…MCL1, a pro-survival and pro-proliferative factor, plays a critical role in many tumor types. The deubiquitination and stabilisation of MCL1 was considered to be required for the proliferation of CC cells ( Morgan et al, 2021 ). What’s more, MCL1 siRNA-silencing demonstrated high efficacy on CC cell lines ( Lechanteur et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…On an opposite direction, other studies show that USP13 may act as an oncogene. For instance, USP13 stabilizes c-Myc that leads to an increased proliferation of glioma cells ( 14) and Mcl-1, which seems to increase proliferation of lung, ovarian and cervical cancer cells (13,31). Moreover, silencing USP13 decreased cell proliferation in lung metastasis of hepatocellular carcinoma (32) and its overexpression is correlated with poor prognosis and chemoresistance of ovarian cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…USP13 belongs to the USPs and its function in cancer is controversial. A recent study showed that USP13 may act as an oncogene in cervical cancer (13). In the same direction, it has been shown a pro-tumor role of USP13 in glioblastoma (14).…”
Section: Introductionmentioning
confidence: 93%
“…Mcl-1 has a short half-life and its expression is regulated by a variety of survival signals [28]. Multiple E3 ligases and deubiquitinases have been identi ed to control ubiquitination and proteasome mediated degradation of Mcl-1 [29][30][31][32]. In addition, Mcl-1 is structurally different from other Bcl-2 anti-apoptotic members at the long amino terminus, which contains two PEST domains, rich in proline(P), glutamic acid(E), serine(S) and threonine(E) amino-acid residues [24].…”
Section: Discussionmentioning
confidence: 99%